A comparative study of the ultrasonographic and morphologic appearance of the normal and abnormal human placenta - Muller, Linda Maria Magdalena (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph.D.(Med.)) -- University of Stellenbosch, 1986.